(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1863)
The author discusses the architecture and owners of the Balmerino mansion in Leith. He quotes Daniel Wilson’s description of the building and its architectural styles, as well as W H Cooper’s then account of the building’s ownership. The second half of the article describes Arthur, the last Baron of Balmerino, who was executed as a Jacobite in 1746.